Exploring social media influences on vaccine decision-making in parents: a netnography - Susan E. Smith; Nina Sivertsen; Lauren Lines; Anita De Bellis (SAGE Publishing, 2024)
Background: Immunization is one of the most significant health initiatives of recent times. Despite this, vaccine hesitancy is increasing and was listed as one of the top 10 threats to global health by the World Health Organization in 2019. A major factor associated with vaccine hesitancy is thought to be the viral spread of misinformation by a small but active anti-vaccination movement. Objectives: The purpose of this study was to explore the influences of social media on vaccine decision-making in parents. Design: This study is part of a larger body of research that explored vaccine decision-making in parents. Other methods included were an online survey and semi-structured interviews. This study investigated the influence of cyberculture on parents in an online environment. Method: This study employed netnography, a form of qualitative inquiry with its roots in ethnography as methodology and a purpose-designed Facebook page as the means of exploring a purpose-designed online community with a particular focus on the culture, belief systems and influences present. Both manual and computer-assisted thematic analyses were used to analyse the data obtained. Results: Three key themes were identified in this study. These included vaccine safety concerns, the emotional debate and COVID-19-specific issues. The results indicated the presence of strong anti-vaccination sentiment combined with an 'infodemic' of conspiracy theories, misinformation and vitriol with the potential to negatively impact parents seeking immunization information. Conclusion: Given the popularity and accessibility of social media and the ready access to misinformation present online, it is evident that parental vaccine decision-making may be impacted adversely. Therefore, it is important that healthcare professionals are aware of this and provide adequate and timely education prior to parents seeking information on social media.